An introduction to floor-managing - Halliday, Eric.; Sanders, Mark.; First Light Video Publishing (United States : First Light Video Publishing, 2010)
Details responsibilities of the floor manager, who is the director's representative on the studio floor, and shows how the job is accomplished.
Producer, Eric Halliday ; director, Mark Sanders.
Keywords: Television -- Production and direction; Television -- Stage-setting and scenery